Effects of cryogenic treatment on mechanical property and microstructure of JIS SKH51 high-speed steel. Issue 1 (November 2015) - Wu, C C; Chen, W C; Chen, L H
Abstract: When SKH 51 high-speed steel was first cryogenically treated and then tempered at 540 °C, the surface hardness of the SKH 51 steel increased from HRC 64 to HRC 65. This result indicates the reduction of retained austenite as well as the secondary precipitation of tiny carbides. TEM analyses indicated that cryogenic treatment can induce high-density dislocations and stacking faults within the martensite matrix. In the subsequent tempering process, conducted at 540 °C, tiny secondary carbides precipitated nearby the existing dislocations and stacking faults, resulting in the hardening of SKH 51 high-speed steel. These secondary carbides mainly consisted of V-rich MC carbides and (Mo, W)-rich M2 C carbides, which were identified by STEM/EDS techniques. After being cryogenically treated and then tempered at 590°C, both the surface hardness and wear resistance of SKH 51 high-speed steel were weakened below acceptable ranges. This result indicates the promotion of rapid decomposition and growth of tempered martensite. Therefore, to achieve the best surface hardness, SKH 51 high-speed steel should first be cryogenically treated, and then tempered at a temperature below 590°C.